The short writings of Nelson Algren a study of his stories, essays, articles, reviews, poems and other literature - Bales, Richard F. 1951- (McFarland & Company, Inc., Publishers, 2022)
"Nelson Algren was a renowned Chicago writer, known for his social commentary and his novels like The Man with the Golden Arm and A Walk on the Wild Side. Although Nelson Algren continues to be remembered almost exclusively for his novels, this book aims to challenge that prevailing perception by highlighting the value and influence of his short form works. Before the author died in 1981, Algren had amassed a genre-defying body of work, including short stories, articles, poems and book reviews. This close reading features a comprehensive analysis and discussion of Algren's lost literature, including everything but his novels. One of the pieces covered is a masterpiece of race relations written in 1950, more than sixty years before the galvanization of the Black Lives Matter movement. Another is a scathing poem about Algren's transatlantic love affair with Simone de Beauvoir. Both items are reprinted in the book courtesy of the Algren estate. This book also includes references to publications containing Algren's work that have yet to be studied by Algren scholars"--